2017
DOI: 10.1097/md.0000000000006150
|View full text |Cite
|
Sign up to set email alerts
|

Reducing effect of aerobic exercise on blood pressure of essential hypertensive patients

Abstract: Background:The comprehensive meta-analysis aimed to explore the reductive effect of aerobic exercise on blood pressure of hypertensive patients.Methods:The related researches were selected from PubMed and Embase databases up to June 2016. Based on specific inclusive criteria, the eligible studies were selected, and the heterogeneities in their results were estimated by χ2-based Q-test and I2 statistics. Quantitative meta-analysis was assessed by R 3.12 software, and results were presented by standardized mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 44 publications
1
39
1
10
Order By: Relevance
“…Another comorbidity, hypertension was predicted by unhealthy sleeping behavior, alcohol consumption, and low exercise levels. It would be expected that hypertension was predicted by unhealthy exercise as aerobic exercise has significant favorable impacts on blood pressure ( Wen & Wang, 2017 ). While exercise has been espoused as a health promotion practice that appeals to many men, a recent review by Bottorff, Oliffe, et al (2015) revealed few programs that were explicitly designed for men, and/or formally evaluated ( Bottorff, Seaton, et al, 2015 ; Caperchione et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another comorbidity, hypertension was predicted by unhealthy sleeping behavior, alcohol consumption, and low exercise levels. It would be expected that hypertension was predicted by unhealthy exercise as aerobic exercise has significant favorable impacts on blood pressure ( Wen & Wang, 2017 ). While exercise has been espoused as a health promotion practice that appeals to many men, a recent review by Bottorff, Oliffe, et al (2015) revealed few programs that were explicitly designed for men, and/or formally evaluated ( Bottorff, Seaton, et al, 2015 ; Caperchione et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The existing exercise recommendations for hypertension advocate that with regards to frequency, aerobic exercise should be undertaken on most (preferably all) days of the week and resistance exercise on 2 to 3 days in that same week [20]. With regards to intensity, the recommendation is for moderate intensity aerobic exercise (i.e., 40 to <60% of maximal oxygen uptake or heart rate reserve; [11][12][13] rating of perceived exertion on the 6-20 Borg Scale and moderate intensity dynamic resistance exercise (60% to 80% one repetition maximum) [20]. In terms of time, the duration of exercise should total 150 min or more per week [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the last decades alternative therapies such as physical exercise have been gaining notoriety for the important beneficial effects on blood pressure of patients with systemic arterial hypertension [8][9][10]. Indeed, a plethora of studies showed that physical exercise may be a potential nonpharmacological treatment for the improvement of blood pressure in patients with hypertension [11]. Because of these effects, some authors have suggested that exercise may reduce or even replace pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation for the difference in ACE-inhibitors may relate to the physically active lifestyle of the ATH-MI group. Physical activity is related to a favourable blood pressure, 17 which may have enabled ATH-MI group members to reduce their medication. Interestingly, ATH þ MI group members reported an increase in activity levels after the MI compared to before, whereas the SED þ MI group members did not change their physical activity behaviour.…”
Section: Discussionmentioning
confidence: 99%